2023
DOI: 10.24996/ijs.2023.64.5.10
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Exudation and Allelopathic Potential of Sunflower Residues as Sustainable Weed Management

Abstract: Total releasing phenolic compounds and allelopathic potential of the three sunflower genotypes Helianthus annuus L. residues were evaluated under open field conditions on weed flora associated with the proposed crops; wheat, broad bean and flax which are cultivated usually after the sunflower crop as successive crops. After getting seed from the sunflower crop. After getting seeds, sunflower plant parts were chopped and incorporated with field soil using a rotavator. Regarding the phenolics, total phenolic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…The number of capsules per plant was directly proportional to the increase in removal periods, Removing weeds for three, four, and five weeks came at the same level of significance with the weedy-free treatment. These results support previous studies, which confirmed that increasing the weed removal periods leads to improving yield components, including the number of capsules per plant [6,12,14]. As for sesame varieties, Had variety excelled with the highest average for this trait 178.3, which did not differ significantly from the Wadaa variety, which recorded the number of capsules per plant at 169.8.…”
Section: Number Of Capsules Per Plantsupporting
confidence: 90%
See 1 more Smart Citation
“…The number of capsules per plant was directly proportional to the increase in removal periods, Removing weeds for three, four, and five weeks came at the same level of significance with the weedy-free treatment. These results support previous studies, which confirmed that increasing the weed removal periods leads to improving yield components, including the number of capsules per plant [6,12,14]. As for sesame varieties, Had variety excelled with the highest average for this trait 178.3, which did not differ significantly from the Wadaa variety, which recorded the number of capsules per plant at 169.8.…”
Section: Number Of Capsules Per Plantsupporting
confidence: 90%
“…The acceptable final seed loss rate was estimated based on previous studies [10,11]  Statistical Analysis: The SASS 9.0 version was used to conduct a statistical analysis of the data by the experimental design and the least significant difference test (L.S.D.) was employed to compare the arithmetic means of the data at a significance level of 0.05 [12].…”
Section: Methodsmentioning
confidence: 99%
“…Substances released by plants with allelopathic properties can suppress the germination and development of nearby or succeeding plants [7,8]. Sunflowers are one of the most widely known allelopathic plants, so new data on the behaviour of these plants among other plants are sought [3,4,9,22,27,28]. Sunflowers accumulate water-soluble allelochemicals in their above-ground organs and roots [9,11,19].…”
Section: Discussionmentioning
confidence: 99%